Increasing competitiveness and assistance in culinary business legality for Islamic council members - Muhammad A. Mahmuddin; Zainal Abidin; Titik Sri Harini; Hironnymus Jati; Lewi Jutomo; Yuliana Tandi Rubak (Universitas Muhammadiyah Magelang, 2023)
This community service aims to: 1) increase partners' awareness of the value of business legal ownership through education and outreach; 2) increase partners' understanding of food safety as a prerequisite for obtaining P-IRT; and 3) help partners obtain legality digitally. The service method involves socialization, training, and assistance. The results of this activity are increased knowledge, understanding and awareness of partners to have business legality, increased knowledge and skills of partners in food processing that is hygienic, nutritious and safe for consumption. In addition, partners are also working on PIRT permits and Halal certificates. Thus, the competitiveness of the culinary business will increase through wider and safer marketing for consumers.